Determination of the specific interaction between sulfonylurea-incorporated polymer and rat islets - Park, KH; Song, S; Akaike, T (JAPANESE BIOCHEMICAL SOC, 2002)
A SU derivative, mimicking glibenclamide in chemical structure, was synthesized to incorporate it into a water-soluble polymeric backbone as a biospecific and stimulating polymer for insulin secretion. The ability of insulin secretion was examined with different glucose concentrations (3.3 and 11.6 mM). Although the vinylated SU did not exhibit significant activity compared to the control, the SU-incorporated copolymer could enhance insulin secretion as much as or more than glibenclamide did. In this study, a polymer fluorescence-labeled with rodamine-B isothiocyanate was used to visualize the interactions and we found that the labeled polymer was strongly absorbed to rat islets, probably due to its specific interaction mediated by SU receptors on the cell membrane. To verify the specific interaction between the SU (K+ channel closer)-incorporated copolymer and rat islets, cells were pretreated with diazoxide, an agonist of ATP-sensitive K+ channels (K+ channel opener), before adding the incorporated polymer to the cell culture medium. This treatment suppressed the action of SUs on rat islets. A confocal laser microscopic study further confirmed this interaction. The results of this study provided evidence that the SU-incorporated copolymer stimulates insulin secretion through specific interactions of SU moieties in the polymer with rat islets.
Keywords: PANCREATIC BETA-CELL; BIOHYBRID ARTIFICIAL PANCREAS; INSULIN-SECRETION; PROTEIN-PHOSPHORYLATION; RECEPTOR; DOGS; IMPLANTATION; LANGERHANS; DIAZOXIDE; COPOLYMER